Embodying modernity : race, gender, and fitness culture in Brazil - Silva, Daniel F., 1985- (Illuminations (Pittsburgh, Pa.), 2022)
"Since the late twentieth century, mainstream popular culture in Brazil has developed an intimate relationship with fitness culture-a vast, fluid, and pervasive network of images and commodities, bodies of knowledge, and discourses pertaining to idealized corporality and personhood. Embodying Modernity works toward a conceptualization of fitness culture, tracing its development and locating its broad existence in the contemporary Brazilian public sphere. Silva examines the role of fitness culture and the visualization of "fit bodies" within the history of western imperialism and its existing discourses of white supremacy, gender binarism, patriarchy, ableism, and heterosexism that continue to define Brazilian nationhood and power structures. Fitness culture in Brazil has developed within and through projects of national modernity and modernization carried out by national elites looking to build a national population aligned with Eurocentric cultural practices and notions of normative bodies"--